Impact of quality of life in patients with chronic kidney disease on the progression of renal function - XIAO Xiao-fen; HAN Si-ping; WANG Xiao-qin (Linchuang shenzangbing zazhi)
Objective To understand the quality of life in patients with chronic kidney disease(CKD)at stages 2,3 and 4 without renal replacement treatment,and to identify its influence on the progress of renal functioa Methods We regularly assessed the quality of life in 138 patients wiht CKD at stages 2,3 and 4 from Hubei Provincial Hospital of Traditional Chinese Medicine and the serum creatinine levels were determined in two years.The gender,age,course of the disease,primary disease,blood pressure,height and weight recorded in all patients,and the body mass index(BMI)was calculated.The quality of life among the three stages was compared.All patients were divided into progressive renal function group and non-progressive renal function group.The basic information and quality of life were compared,and the risk factors for progression of renal function were analyzed by nonconditional Logistic regression analysis.Results ①The scores of all 10 dimensions on quality of life in CKD stage 4 group were lower than those in CKD stage 3 and CKD stage 2 groups,and there was significant difference in influence of symptoms,influence of kidney disease,physical function,social function,and physical energy(P<0.05).②The BMI was lower in the progression group than in the non-progression group(P<0.05).On the 10 dimensions of quality of life,the scores in the progression group were lower than in the non-progression group.There was significant difference in influence of symptoms,influence of kidney disease,kidney disease burden,physical function,emotional status,socioemotion,and physical energy(P<0.05).③BMI,influence of symptoms,physical function,and emotional status were risk factors for progression of renal function.Conclusions Quality of life in patients with CKD was declined along with the reduction of glomerular filtration rate,and that in patients with renal progress is worse.Influence of symptoms,physical function and emotional status are the risk factors for progression of renal function,suggesting the CKD patients may be in the vicious cycle of disease affecting quality of life and poor quality of life accelerating the progression of renal function.Concerning the quality of life in patients with CKD is essential.